Monitoring Pembangkit Listrik Tenaga Surya Berbasis Arduino dengan Media Telegram - Tamam, M. Taufiq; Aditia, M. Indra (UM Purwokerto Press, 2023)
The implementation of monitoring the performance parameters of the PLTS system in several regions is still done manually so that the data obtained is also limited. In this study the PLTS monitoring system is based on Arduino Uno so that monitoring on PLTS can be monitored with telegram media. The monitoring system has two inputs, namely for PV and for the battery. To monitor the value of the electrical energy parameter, the INA219 sensor is used. The sensor reading results are displayed on the 16x2 LCD and mobile phone by sending the